Experimental study of mupirocin ointment influence in S.aureus polyresistant clinical strains, isolated from patients with allergodermatosеs - Dzhoraieva, Svitlana; Kutasevich, Yanina; Sobol, Natalya; Goncherenko, Valentina; Scherbakova, Yulija; Ivantsova, Olena; Schegileva, Olena; Oliinyk , Olga (Annals of Mechnikov's Institute, 2021)
Introduction. Therapy of infectious lesions is complicated due to the growing resistance of the main pathogens of pyoderma – S. aureus і S. epidermidis. From this point of view, there is a constant need to choose an active local antistaphylococcal agent. Global studies have shown that a key component in the treatment of mild or moderate skin infections is the use of topical antibiotics rather than systemic drugs, as they maximize effective doses at the infection focus, minimizing systemic side effects. In addition, the ideal topical antibiotic should be selective (thus minimizing cross-resistance), have low sensibilization potential, effectively penetrate the skin, reach adequate local areas at the site of infection, and finally be available in various dosage forms for external application. The aim of the work: to evaluate the antibacterial activity of the ointment with mupirocin in relation to polyresistant clinical strains of S. aureus, isolated from patients with allergic dermatoses.Materials & Methods: the profile of antibiotic resistance of 142 clinical strains of S. aureus isolated from the affected skin areas of patients with allergic dermatoses was determined, with the determination of the antibacterial effect of the ointment with mupirocin against MRSA and MSSA (49 strains) using the agar diffusion method (method of wells) and its therapeutic efficacy in the treatment of these diseases complicated by secondary infection. Results & Discussion: It is established that S. aureus is the dominant microorganism in the frequency of isolationl from the lesions of patients with allergodermatoses and the most pathogenic member of the genus. Among the isolated S. aureus, 85,2 % of the strains were resistant to penicillin, and 26,7 % of them were so-called MRSA- strains, the presence of which makes it impossible to prescribe the disease of any β-lactam antibiotics. Isolated strains showed moderate resistance to tetracycline, aminoglycosides, fluoroquinolones and lincosamides - 47,9 %, 43,7 % 31,7 % і 27,5 % respectively, and quite high – to macrolides (up to 62,0 %). In addition, 4,2 % vancomycin-resistent strains were detected in structure of antibiotic resistance, which indicates an increase in the aggressive potential of the obtained pathogens. The sensitivity of the removed pathogens was the highest to fusidic acid preparations and to linezolid - 92,3 %, 93,7 % of strains respectively. Based on the monitoring, the presence of 54,2 % MDR- strains and 4,9 % XDR-strains was detected. Exactly 49 clinical multidrug-resistant strains were selected for detailed determination of the antibacterial action of mupirocin. It was found that mupirocin actively suppressed the growth of both MRSA and MSSA strains. Not a single clinical strain from the 49 investigated ones, resistant to mupirocin was identified. The ointment with mupirocin exhibits a highly effective antibacterial effect against clinical multi-resistant S. aureus strains (including MRSA strains). As a result of the use of an ointment with mupirocin for external treatment of patients with allergic dermatoses during an exacerbation, regression of clinical signs of pyococcal infection was noted in 81.3% of individuals. Concluzion Ointment with mupirocin has a highly effective antibacterial effect against clinical multidrug-resistant strains S. aureus (including MRSA strains), which makes it possible to recommend its use as a first-line drug for external therapy of microbial complications of allergic dermatoses. According to the above data, mupirocin claims to the place in the standarts of treatment in the first link of antibacterial drugs for external use. Keywords: clinical strains of S. aureus, antibiotic resistance, external antibiotic therapy, mupirocin. DOI: 10.5281/zenodo.5499680